Performance of a Qualitative Point-of-Care Strip Test to Detect DOAC Exposure at the Emergency Department: A Cohort-Type Cross-Sectional Diagnostic Accuracy Study - Merrelaar, Anne E.; Bögl, Magdalena S.; Buchtele, Nina; Merrelaar, Marieke; Herkner, Harald; Schoergenhofer, Christian; Harenberg, Job; Douxfils, Jonathan; Siriez, Romain; Jilma, Bernd; Spiel, Alexander O.; Schwameis, Michael (Thrombosis and Haemostasis, 2022)
An accurate point-of-care test for detecting effective anticoagulation by direct oral anticoagulants (DOACs) in emergencies is an unmet need. We investigated the accuracy of a urinary qualitative strip test (DOAC Dipstick) to detect relevant DOAC exposure in patients who presented to an emergency department. In this prospective single-center cohort-type cross-sectional study, adults on DOAC treatment were enrolled. We assessed clinical sensitivity and specificity of DOAC Dipstick factor Xa and thrombin inhibitor pads to detect DOAC plasma levels ≥30 ng/mL using urine samples as the testing matrix. Liquid chromatography coupled with tandem-mass spectrometry was used as the reference standard method for plasma and urine measurement of DOAC concentrations. Of 293 patients enrolled, 265 patients were included in the analysis, of whom 92 were treated with rivaroxaban, 65 with apixaban, 77 with edoxaban, and 31 with dabigatran. The clinical sensitivity and specificity of the dipstick on urine samples to detect ≥30 ng/mL dabigatran plasma levels were 100% (95% confidence interval [CI]: 87–100%) and 98% (95% CI: 95–99%), respectively. The sensitivity and specificity of the dipstick to detect ≥30 ng/mL factor Xa inhibitor plasma levels were 97% (95% CI: 94–99%) and 69% (95% CI: 56–79%), respectively. The DOAC Dipstick sensitively identified effective thrombin and factor Xa inhibition in a real-world cohort of patients presenting at an emergency department. Therefore, the dipstick might provide a valuable test to detect relevant DOAC exposure in emergencies, although further studies will be needed to confirm these findings.
Keywords: cohort study; anticoagulants; direct thrombin inhibitor; direct factor Xa inhibitors; point-of-care-test